Forecasting factors and outcomes in hawkish inflammatory breast carcinoma - A single center data exploration. (2022) - Selvarajan, Gangothri; Radhakrishnan, Venkatraman; Jayachandran, Perumal Kalaiyarasi; Subramaniam Murali, Carthikeyan; Velusamy, Sridevi; Krishnamurthy, Arvind; Iyer, Priya; Ananthi, Balasubramanian; Ganesarajah, Selvaluxmy; Sagar, Tenali Gnana
Highlights: Retrospective analysis of aggressive inflammatory breast carcinoma showed favourable EFS and OS benefits for those who had clinical response to neoadjuvant (CR+PR) and received locoregional treatment to primary tumor in non-metastatic patients. Presence of post-menopausal status, grade2, Ki67 ≤ 50%, N1/N2stage and single site of metastases in stage IV displayed better survival outcomes. Presence of higher proportion of premenopausal status, lesser HR expression, lesser pCR rates, higher N3 proportion, liver metastasis and multiple metastatic site involvement contributed to the worse outcome observed in this study. Abstract: Introduction: Inflammatory breast carcinoma (IBC) is an aggressive clinical syndrome of invasive breast carcinoma. There is paucity of data regarding the outcomes in IBC. Objectives: Analyses of OS and Event-free survival (EFS) in nonmetastatic and metastatic IBC and to find prognostic factors influencing them. Methodology: In this single center, retrospective study the data of patients fulfilling the clinical criteria of IBC were retrieved from 2016 to 2021. The impact of prognostic factors on OS and EFS were analysed by log rank test (univariate analysis). The OS and EFS were depicted as Kaplan Meier survival curves. Results: There were 22 patients with IBC. Median follow-up was 17 months. The median OS was significantly better in non-metastatic(M0) compared to metastatic IBC (25 months vs 6 months) with 3year OS rate of 50% vs 0% respectively. The post-menopausal status, grade 2 histology and trimodality treatment showed better outcome while N3 stage at diagnosis had worse outcome in M0 group. The lesser HR expression, lesser pCR rates, higher N3 proportion, liver metastasis and multiple metastatic site involvement contributed to the worse outcome observed in this study. Conclusion: The aggressive clinicopathological features of IBC in the present study resulted in less favourable outcome compared to literature review. Improved outcome with trimodality highlights the emergent need for additional targeted therapy to improve pCR and operability.